(untitled) (JEMARI (Jurnal Edukasi Madrasah Ibtidaiyah), 2024)
Abstrack The development of the use of Javanese Krama is influenced by educational practices and models at home, school, and the surrounding environment. Many parents often accustom their children to using Ngoko, Indonesian, and even English rather than using Javanese krama. Sadly, students who do not master the Javanese language are very much found. This study aims to determine the effect of the games-based learning model on the Javanese language skills of fifth grade students at SD Negeri 03 Sekuro in the 2023/2024 school year. This research method includes quantitative research with pre-test and post-test one group design. The research site was located at SD Negeri 03 Sekuro and the population in this study were all students in class V, while the sample was taken as many as 12 class V students. Data collection techniques using observation and tests. Based on the results of the t test calculation obtained tcount is 8.022 while the t table is 1.796. Because tcount> t table is 8.022> 1.796 then the t test learning model games based learning affects the skills of Javanese language manners class V SD Negeri 03 Sekuro. Keyword: Language Skills, Games, Learning Abstrak Perkembangan penggunaan bahasa Jawa Krama dipengaruhi oleh praktik dan model pendidikan di rumah, sekolah, dan lingkungan sekitar.Ada banyak Orang tua kerap membiasakan anak-anaknya menggunakan bahasa Ngoko, bahasa Indonesia, bahkan bahasa inggris daripada menggunakan bahasa Jawa krama. Mirisnya peserta didik yang kurang menguasai bahasa Jawa krama inggil sangatlah banyak dijumpai. Peneletian ini bertujuan mengetahui pengaruh model games based learning terhadap keterampilan berbahasa Jawa krama siswa kelas V di SD Negeri 03 Sekuro tahun ajaran 2023/2024. Metode Penelitian ini termasuk jenis penelitian kuantitaif dengan design pre-test dan post-test one group design. Tempat penelitian berlokasi di SD Negeri 03 Sekuro dan populasi dalam penelitian ini adalah seluruh siswa dikelas V, Sementara sampel diambil sebanyak 12 siswa kelas V. Teknik pengumpulan data mengunakan observasi dan tes. Berdasarkan hasil hitung uji t diperoleh thitung adalah 8.022 sedangkan ttabel yaitu 1.796. Karena thitung > ttabel yaitu 8.022 > 1.796 maka uji t model pembelajaran games based learning berpengaruh terhadap keterampilan berbahasa Jawa krama kelas V SD Negeri 03 Sekuro Kata kunci: Ketrampilan Bahasa, Games, Learning